Месопотамия и Бактрия во II тыс. до. н.э. - Сарианиди, В. И.
Sarianidi, V. I., Mesopotamia and Bactria in the 2nd Mill. B.C.; engl. Résumé; Material aus Baktrien / Margiana mit iranisch-mesopot. Prototypen; u.a. Siegelzylinder.